2021
DOI: 10.3390/jpm11070612
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers for Homologous Recombination Deficiency in Cancer

Abstract: DNA double-strand breaks foster tumorigenesis and cell death. Two distinct mechanisms can be activated by the cell for DNA repair: the accurate mechanism of homologous recombination repair or the error-prone non-homologous end joining. Homologous Recombination Deficiency (HRD) is associated with sensitivity towards PARP inhibitors (PARPi) and its determination is used as a biomarker for therapy decision making. Nevertheless, the biology of HRD is rather complex and the application, as well as the benefit of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 56 publications
1
38
0
Order By: Relevance
“…Recent clinical studies using olaparib monotherapy for TNBC showed promising response in HRD high patients [ 58 ]. Among the current HRD screening tests in clinic only two (Myriad’s myChoice ® CDx and HRD Focus Panel) screen for TAI in patient samples to account for HRD [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent clinical studies using olaparib monotherapy for TNBC showed promising response in HRD high patients [ 58 ]. Among the current HRD screening tests in clinic only two (Myriad’s myChoice ® CDx and HRD Focus Panel) screen for TAI in patient samples to account for HRD [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Separately, both preclinical and preliminary clinical data have shown that patients who have mutations in HR repair genes other than BRCA1/2 can benefit from PARPi therapy. 42 , 91 , 92 The prevalence of these mutations across non-reproductive solid tumors has been reported to be less than 20%, 93 and the rarity of these alterations makes developing clinical trials with sufficient statistical power to demonstrate the benefit of PARPi in these populations a challenge. Multiple companies have off-the-shelf targeted sequencing panels that include HR repair genes “beyond” BRCA1/2 , and Table 1 summarizes the use of these non- BRCA1/2 HR repair genes as eligibility criteria in currently recruiting PARPi clinical trials listed on clinicaltrials.gov.…”
Section: Hr Deficiency Testing In the Clinicmentioning
confidence: 99%
“…Ultimately, interpreting the relevance of HR-related mutations is likely still to be dependent on the clinical and histological context of a patient, as few of these mutations predict for PARPi benefit outside of reproductive cancers. 34 , 92 …”
Section: Hr Deficiency Testing In the Clinicmentioning
confidence: 99%
“…Another emerging point of our results was the relationship between the tumor morphology, AKT isoforms and HR status. Considering the incompleteness of the HR status by BRCA1/BRCA2 genetic testing [ 33 ] as well as the expensiveness of current multigene panels for HRD testing, the prediction of homologous recombination proficiency/deficiency by means of AKT ratios, SET and BRCA1 expression could be of particular interest as a possible surrogate. Despite the small sample size, our logistic regression analysis suggested that the simultaneous assessment of the abovementioned features could be useful at least in discriminating tumors with somatic pathologic mutations on BRCA1 or BRCA2 genes, also resulting in a good level of sensitivity and specificity (0.75; 0.97 − AUC = 0.88).…”
Section: Discussionmentioning
confidence: 99%